Limited Foxp3+ Regulatory T Cells Response During Acute Trypanosoma cruzi Infection Is Required to Allow the Emergence of Robust Parasite-Specific CD8+ T Cell Immunity - Araujo Furlan, Cintia L.; Tosello Boari, Jimena; Rodriguez, Constanza; Canale, Fernando P.; Fiocca Vernengo, Facundo; Boccardo, Santiago; Beccaria, Cristian G.; Adoue, Véronique; Joffre, Olivier; Gruppi, Adriana; Montes, Carolina L.; Acosta Rodriguez, Eva V. (Frontiers in Immunology, 2018)
While it is now acknowledged that CD4+ T cells expressing CD25 and Foxp3 (Treg cells) regulate immune responses and, consequently, influence the pathogenesis of infectious diseases, the regulatory response mediated by Treg cells upon infection by Trypanosoma cruzi was still poorly characterized. In order to understand the role of Treg cells during infection by this protozoan parasite, we determined in time and space the magnitude of the regulatory response and the phenotypic, functional and transcriptional features of the Treg cell population in infected mice. Contrary to the accumulation of Treg cells reported in most chronic infectious diseases, T. cruzi infection was characterized by sustained numbers but decreased relative frequency of Treg cells. The reduction in Treg cell frequency resulted from a massive accumulation of effector immune cells, and inversely correlated with induction of the effector immune response as well as with emergence of acute immunopathology. In order to understand the causes underlying the marked reduction in Treg cell frequency, we evaluated the dynamics of the Treg cell population and found a low proliferation rate and limited accrual of peripheral Treg cells during infection. We also observed that Treg cells became activated and acquired a phenotypic and transcriptional profile consistent with suppression of type 1 inflammatory responses. To assess the biological relevance of the relative reduction in Treg cells frequency observed during T. cruzi infection, we transferred in vitro differentiated Treg cells at early moments, when the deregulation of the ratio between regulatory and conventional T cells becomes significant. Intravenous injection of Treg cells dampened the induction of parasite-specific CD8+ T cells immunity and affected parasite control in blood and tissues. Altogether, our results show that limited Treg cell response during the acute phase of T. cruzi infection enables the emergence of protective anti-parasite CD8+ T cell immunity and critically influences host resistance.